Understanding the action-based research for strategic change from systemic perspectives - Jae Eon Yu (Global Business & Finance Review (GBFR), 2021)
Purpose: This study aims to serve a wider range of understandings about how the systems-based approach (e.g. SSM and VSM) of different strategic initiatives can help Korean company to utilize the strategic HRM in association with the development of the PMS or making a sustainable development within environmental changes. Design/methodology/approach: The study conducted an action-based research, using Soft Systems Methodology (SSM) and Viable System Model (VSM), which was applied in the field of strategic HRM and PMS (Performance Management Systems) with support from a case study of the Korean company. The data collection process includes in-depth interviews with general manager and participants from Korean company named ACE, which operates at Daegu, South Korea. Findings: Prior studies of the PMS based BSC tend to inquiry and examine the proposed model for PMS from the hard HRM tradition. This study on the PMS from the soft tradition using systems approach tends to operating well within management practice. The findings indicate that an action-based research based on the combined use of SSM and VSM approach is useful for understanding the nature of strategic HRM in association with PMS within the organization. Research limitations/implications: This study was aimed to understand and appreciate the value of an action-based research through the systemic intervention using SSM and VSM in the fields of strategic HRM in association with PMS. Therefore, it difficult to generalize the performance management systems that can be applied in other contexts. Originality/value: This study taken to develop the Performance Management Systems, which was based on the systems approach namely Checkland's soft systems methodology and Beer's viable system model, to understand and appreciate the value of PMS within the Korean company.
Keywords: 650; Strategic HRM; Performance Management Systems; action-based research; soft systems methodology